Синтез информационо-логической модели компьютеризированной системы оперативного управления конкурентоспособностью предприятия - Тимофеев, В. А.; Лещенко, Е. В. (ХНУРЭ, 2014)
The structure of information and logical model of a computerized system of operational management of the enterprise competitiveness (EC) has been developed. The model allows taking into account in complex: the value of the integral indicator of competitiveness and strategic positioning of the company on a given segment of the consumer market – in the process of management; to correct trend of the indicator of effectiveness of EC management adaptively to the conditions of production and the requirements of the consumer market.
Keywords: конкурентоспособность; информационно-логическая модель; методы управления; эффективность управления; конкурентный потенциал; оперативное управление; компьютеризированная система управления